Aerosol Inhalation Delivery of Ag Nanoparticles in Mice: Pharmacokinetics and Antibacterial Action - Sergey V. Valiulin; Andrei A. Onischuk; Alexandra P. Pyryaeva; Sergey V. An'kov; Anatoly M. Baklanov; Nikolay N. Shkil; Ekaterina V. Nefedova; Kirill S. Ershov; Tatyana G. Tolstikova; Galina G. Dultseva (MDPI AG, 2023)
The aerosol inhalation delivery of composite particles consisting of Ag nanoparticles enveloped by polyvinylpyrrolidone was investigated in experiments with mice. An ultrasonic nebulizing system was created for the generation of aerosols with a mean diameter and mass concentration of 700 ± 50 nm and 65 ± 5 mg/m3, respectively. The mass fraction of Ag in the composite particles was α = 0.061. The aerosol delivery was performed in a whole-body chamber with an exposition time of 20 min. Pharmacokinetic measurements were taken and the silver concentrations in the blood and lungs of the mice were measured as a function of time after exposition by means of electrothermal (graphite furnace) atomic absorption spectrometry. The inhalation dose and other pharmacokinetic parameters were determined. The antibacterial effect of aerosolized silver was assessed for mice infected with Klebsiella pneumoniae 82 and Staphylococcus aureus ATCC 25953. The survival rate of the infected mice after the aerosol exposure demonstrated the high antibacterial efficiency of Ag nanoparticles after inhalation delivery.